Frequency of Hyperlipidemia in the Diagnosed Type 2 Diabetic Patients - Shama Iqbal; Ambreen Gul; Rashid Ahmad; Momina Haq; Sara Maryam; Safia Rehman (Gandhara University, 2021)
OBJECTIVES: The primary event in the development of type-2 diabetes is directly associated with lipid metabolism derangement occurring due to insulin resistance. The aim of this study was to find out the prevalence of hyperlipidemia in the newly diagnosed type-2 DM. METHODOLOGY: This hospital based descriptive study was conducted in the year 2018 to 2019, on 100 newly diagnosed type-2 diabetic patients attending medical O.P.D or admitted in medial wards of Naseer Ullah Khan Babar Memorial Hospital Kohat Road Peshawar. RESULTS: The incidence of hyperlipidemia in newly diagnosed diabetic patients was 29%. About 71% patients were having normal lipid profile. Our study also revealed that the frequency of hyperlipidemia increases with age. Half of the patients having age more than 60 years developed hyperlipidemia. Among hyperlipidemic patients, hypercholesterolemia was present in 36% and hypertriglyceridemia in 64% patients CONCLUSION: The study suggests that hyperlipidemia is very common in newly diagnosed type-2 diabetic patients in this part of the world.